Sustainable value chain approach for livestock-based livelihood strategies for communities of the southeastern coast of Bangladesh - Prabal Barua; Syed Hafizur Rahman; Maitri Barua (Modern Supply Chain Research and Applications, 2021)
Purpose - The nature of farm animals in the marginalized group of people is varying hurriedly. Livestock is used to add to cash earnings and increase food security, hence helping as a vital component in the household's source of revenue strategies, particularly at marginal planter's level. The present study was conducted to assess the numbers of livestock farmers in the study areas, their livelihood options, the value chain of the farmers in different marketing channels and recommendation for the sustainable value chain of the livestock production cycle. Design/methodology/approach - The study precise the baseline condition of marginal livestock farmers for access to value chain activities in terms of inputs, outputs, support services, production, yield, income and enabling environment to enhance livestock farming in the study area. The study was conducted through stratified random sampling of the context using some research tools like in-depth interviews, household surveys, expert opinions and focus group discussions. Structured questionnaires were developed to address issues, such as current livestock farming practices, access to support services, capacity and income. Findings - The study revealed that this particular context is lagging behind to establish goat value chain activities in the targeted areas. The farmers do not have basic knowledge of goat farming, and the value chain actors are not working properly. The support services are not appropriate to turn the goat farming production to a standard level. Value chain of livestock and livestock products and their goals are essential to develop an idea on learning, investment, market access, sales assurance and quality. Variation in institutional contexts of end markets is linked to different types of coordination and control of enabling environment throughout the chains. Practical implications - Livestock is an integral component of the complex farming system in Bangladesh as it serves as not only a source of meat protein but also a major source of farm power services as well as employment. Strong private sector alliance along with public-private ventures can bring sustainable agriculture value chain development in these most vulnerable coastal communities in Bangladesh. Strengthening the weak financial structure, reducing power imbalances in the governance structures and low political intervention in community-level organizations, and resolving socio-cultural and environmental concerns are the major concerns on the development of value chains in Bangladesh. Originality/value - Geographical position and climatic condition of Bangladesh have made her coastal areas one of the highly productive areas for livestock production in the world. The study was conducted through qualitative and quantitative analysis, and after finding the authors recommended for sustainable value chain approach for livestock production to a marketing channel for improving the financial condition and self-employment for the communities.
Keywords: 650; Institutional context; Livestock; South-eastern coast of Bangladesh; Sustainability; Value chain